Role of Interleukin-6 in Lung Complications in Patients With COVID-19: Therapeutic Implications - Smetana, Karel; Brábek, Jan (In vivo (Athens, Greece), 2020)
COVID-19 is viral respiratory infection with frequently fatal lung complications in the elderly or in people with serious comorbidities. Lung destruction appears to be associated with a cytokine storm related to an increased level of interleukin-6 (IL6). Therapeutic targeting of the interleukin-6 signaling pathway can attenuate such a cytokine storm and can be beneficial for patients with COVID-19 in danger of pulmonary failure. This article demonstrates the importance of IL6 in progression of disease and the possibility of inhibition of IL6 signaling in COVID-19 therapy.
Keywords: virové receptory; Interleukin-6; Receptors, Virus; indoly; plíce; SARS-CoV-2; Cytokine Receptor gp130; cytokine storm; review; koronavirové infekce; Antiviral Agents; interleukin-6; Humans; lung failure; receptory interleukinu-6; virová pneumonie; Receptors, Interleukin-6; Anti-Inflammatory Agents; klinické zkoušky jako téma; COVID-19; syndrom uvolnění cytokinů; monoklonální protilátky; antiflogistika; IL6; Antibodies, Monoclonal; antivirové látky; imunoterapie; pandemie; Pneumonia, Viral; Antibodies, Monoclonal, Humanized; Clinical Trials as Topic; Indoles; humanizované monoklonální protilátky; Immunotherapy; COVID-19 therapy; cytokinový receptor gp130; lidé; Coronavirus Infections; Signal Transduction; Cytokine Release Syndrome; Pandemics; Lung; signální transdukce